A meta-analysis of mental imagery effects on post-injury functional mobility, perceived pain, and self-efficacy. (January 2018) - Zach, Sima; Dobersek, Urska; Filho, Edson; Inglis, Varda; Tenenbaum, Gershon
Abstract: Objectives: A meta-analysis was employed to examine the effects of mental imagery (MI) on bio-psychological variables, namely functional mobility, perceived pain, and self-efficacy . Method: Ten studies were included in the meta-analytical review. Cohen's d effect sizes (ES) and Hedge's g weighted mean ES (WMES) were computed for all dependent variables. Results: The analysis revealed non-significant effects of imagery interventions that were (1) small and positive for functional mobility ( g = 0.16), (2) large and negative for perceived pain ( g = −0.86), and (3) large and positive for self-efficacy ( g = 0.99). These effects were all non-significant, probably because the interventions administered and populations sampled in the studies were mostly heterogeneous. The observed null results might also reflect that existing studies on injury lack power. Hence, the effects of MI on bio-psychological variables warrant continued empirical investigation. Conclusions: Given the observed statistical trends, MI interventions might be beneficial for athletes recovering from injury. However, more experimental work in needed before one claims with certainty that MI enhances bio-psychological functioning in injured athletes. Highlights: The effect of mental imagery on functional mobility was null, small, and positive ( g = 0.16). The effect of mental imagery on perceived pain was null, large, and negative ( g = −0.86). The effect of mental imagery on self-efficacy was null, large, and positive ( g = 0.99). Original research lacks power and seems to be based primarily on convenience sampling.